IMPACT OF AN UNDERSLUNG LOAD ON A HELICOPTER CONTROLLABILITY - G. N. Babenko; V. V. Efimov; V. A. Ivchin (Научный вестник МГТУ ГА)
This article is aimed at finding the causes of controllability variations of a helicopter while transporting sling load.The maximum angular acceleration taken by the helicopter at similar controller displacement at different flight speeds was taken as a quantity characteristic of controllability efficiency to study the load impact on the helicopter cont- rollability.This article offers research results obtained with the use of the НеliСargо software. This software has proven to be a great tool for integrated research of the impact of an underslung load on the parameters of a helicopter controllability, and allows carrying out an analysis of the impact of an underslung load on the parameters of controllability under its dyna- mic behavior.The performed computational experiments have shown that the helicopter maximum angular acceleration with an underslung load significantly rises, as compared to a helicopter without cargo or a helicopter carrying the same load inside the cargo compartment. The data obtained during computational experiments corresponds to the results of analytical computations, and is in line with the literature based on the experience of helicopter flight operations.The cause of the variation in the helicopter controllability parameters during transportation of an underslung load has been found, that is - the underslung load considerably increases the main rotor thrust, due to sling load, as compared to a helicopter without cargo. When compared to a helicopter carrying a load inside the cargo compartment, this increased efficiency is mainly attributed to the fact that a helicopter with an underslung load has lower rotational inertia, since the load is not inside the cargo compartment, but outside.The obtained results can be used to improve flight manuals and flight personnel training publications, which could play a significant part in ensuring flight safety and security, and increasing the operational efficiency of helicopters with external slung load systems.